The Geriatric Nutritional Risk Index is a powerful predictor of adverse outcome in the elderly emergency surgery patient. Issue 2 (August 2020) - Jia, Zhenyi; El Moheb, Mohamad; Nordestgaard, Ask; Lee, Jae Moo; Meier, Karien; Kongkaewpaisan, Napaporn; Han, Kelsey; El Hechi, Majed W.; Mendoza, April; King, David; Fagenholz, Peter; Saillant, Noelle; et al.
Abstract : BACKGROUND: The degree to which malnutrition impacts perioperative outcomes in the elderly emergency surgery (ES) patient remains unknown. We aimed to study the relationship between malnutrition, as measured by the Geriatric Nutritional Risk Index (GNRI), and postoperative outcomes in elderly patients undergoing ES. METHODS: Using the 2007 to 2016 American College of Surgeons National Surgical Quality Improvement Program database, all patients 65 years or older undergoing ES were included in our study. The GNRI, defined as (1.489 × albumin [g/L]) + (41.7 × [weight/ideal weight]) was calculated for each patient in the database. Patients with missing height, weight, or preoperative albumin data were excluded. Patients were divided into four malnutrition groups: very severe (GNRI < 73), severe (GNRI, 73–82), moderate (GNRI, 82–92), and mild (GNRI, 92–98). Geriatric Nutritional Risk Index greater than 98 constituted the normal nutrition group. Risk-adjusted multivariable logistic regressions were performed to study the relationship between malnutrition—measured using either GNRI, albumin level, or body mass index less than 18.5 kg/m 2 —and the following postoperative outcomes: 30-day mortality, 30-day morbidity (including infectious and noninfectious complications), and hospital length of stay. The relationship between GNRI score and 30-day mortality for six common ES procedures was then assessed. RESULTS: A total of 82, 725 patients were included in the final analyses. Of these, 55, 214 were malnourished with GNRI less than 98 (66.74%). Risk-adjusted multivariable analyses showed that, as malnutrition worsened from mild to very severe, the risk of mortality, morbidity, and the hospital length of stay progressively increased (all p < 0.05). Patients with very severe malnutrition had at least a twofold increased likelihood of mortality (odds ratio [OR], 2.79; 95% confidence interval [CI], 2.57–3.03), deep vein thrombosis (OR, 2.07; 95% CI, 1.77–2.42), and respiratory failure (OR, 1.95; 95% CI, 1.81–2.11). Geriatric Nutritional Risk Index predicted mortality better than albumin or body mass index alone for ES. CONCLUSION: Malnutrition, measured using GNRI, is a strong independent predictor of adverse outcomes in the elderly ES patient and could be used to assess the nutrition status and counsel patients (and families) preoperatively. LEVEL OF EVIDENCE: Prognostic study, Level IV. Abstract : Supplemental digital content is available in the text.